Manufacturing process of ETPU sole
Through the steam forming process of TPU outsole and ETPU foamed particles, combined with the fiber mesh layer of ultra-high molecular weight polyethylene fiber-loaded carbon nanotubes, the problem of insufficient bonding strength between ETPU shock-absorbing midsole and rubber outsole is solved, efficient and environmentally friendly sole production is achieved, and the performance and recycling of the sole are improved.
Patent Information
- Application Number
- CN202411972141.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
AI Technical Summary
The bonding strength between the existing ETPU shock absorbing midsole and the rubber outsole is insufficient, and the process is cumbersome, making it difficult to recycle.
The TPU outsole and ETPU foamed particles are integrally formed by steam forming, and the texture-containing mold is used to form the texture during molding, saving the preforming process, and improving the bonding strength through the fiber web layer of the carbon nanotube loaded with ultra-high molecular weight polyethylene fibers.
It improves the bonding strength between the TPU outsole and the ETPU midsole, simplifies the process flow, facilitates recycling, and improves the wear resistance, slip resistance and tensile resistance of the sole.
Smart Images

Figure CN119610722A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sole production technology, and more specifically, it relates to a manufacturing process of ETPU soles. Background Art
[0002] E-TPU foam material is a new type of polymer material composed of countless elastic and lightweight TPU foam balls. It is composed of amorphous and rigid molecular chains and does not contain any flexible segments in its molecular structure. Therefore, ETPU material has both the strength and dimensional stability of amorphous resins and the chemical resistance, fatigue resistance and wear resistance of crystalline resins.
[0003] ETPU material overcomes the shortcomings of TPU raw materials such as heavy weight, high hardness, and poor shock absorption performance. At the same time, it is lighter, more breathable, environmentally friendly, wear-resistant, highly elastic, and resistant to yellowing. It is suitable for products that need to withstand strong impact and frequent use, require transparency, dimensional stability, and excellent chemical resistance, such as: sports shoe midsoles.
[0004] At present, in order to achieve wear-resistant and non-slip bottom of ETPU shock-absorbing midsole, a wear-resistant rubber bottom sheet is set at the bottom of ETPU midsole. The composite of ETPU midsole and rubber bottom sheet is usually bonded and connected by glue, but glue bonding increases the sole manufacturing process, and the glue has a heavy odor and poor environmental protection. In the prior art, the Chinese invention patent application document with application number CN2020104740602 discloses a one-piece molding process of ETPU shock-absorbing midsole and rubber outsole, in which the rubber sheet is cut and cleaned, and the rubber outsole is made and placed at the bottom of the steam molding mold, ETPU particles are added, and the ETPU particles are heated by water vapor to make the surface of the ETPU particles molten. After pressing, the ETPU particles are bonded to the rubber outsole.
[0005] However, due to the material differences between the rubber outsole and the ETPU particles, the compatibility is poor, the adhesion is insufficient after one-piece molding, and the rubber outsole is easily separated from the ETPU foaming particles. In addition, due to the differences in the melting point molding processes of the two materials, the texture structure on the rubber outsole needs to be vulcanized in the mold in advance and then integrated with the ETPU particles. The operation is more cumbersome, and the rubber outsole and ETPU particles are difficult to recycle and apply together, which is not conducive to recycling. Summary of the invention
[0006] In order to increase the bonding strength between the midsole and the outsole, facilitate the recycling of the two together, and eliminate the need for pre-formed patterns on the outsole, the present application provides a process for manufacturing an ETPU sole.
[0007] In the first aspect, the present application provides a manufacturing process of an ETPU sole, which adopts the following technical solution: A manufacturing process of ETPU soles, comprising the following manufacturing steps: Making TPU outsole: cutting the TPU bottom sheet into the required shape to obtain the TPU outsole; Injection: Lay the TPU outsole in the midsole forming mold with a textured cavity, and then fill the midsole forming mold with ETPU foaming particles so that the ETPU foaming particles are laid on the upper surface of the TPU outsole; Steam molding: Steam is introduced into the midsole molding mold to mold the ETPU particles into the ETPU midsole. The molding pressure is 0.1-0.3MPa, the molding temperature is 120-160℃, and the molding time is 150-190s. Then, the mold is vented, water-cooled, and demolded to obtain the ETPU sole.
[0008] By adopting the above technical solutions, the TPU outsole has high strength and hardness, can withstand daily wear and impact, maintain the shape and stability of the shoe, and also has high toughness, and is not easy to break or damage when subjected to external forces. The TPU outsole also has excellent wear resistance and aging resistance, can resist long-term friction and wear, extend the service life of the shoe, can maintain stable performance under different climate conditions, is not easy to age or deform, and has good elasticity, can adapt to the movement needs of the foot, achieve lightweight, provide a comfortable wearing experience, and can effectively relieve the force on the foot and reduce foot fatigue. The midsole adopts ETPU The particles are in a popcorn shape after molding, have excellent resilience and deformation recovery, and their performance far exceeds that of traditional EVA materials. They also have excellent wear resistance and low temperature resistance, ultra-light density, excellent environmental protection, good flex resistance, yellowing resistance, and good resilience. In addition, a cavity containing patterns is provided in the midsole molding mold, and the TPU outsole is placed first. During molding, patterns can be formed on the TPU outsole while the ETPU particles and the TPU outsole are integrally molded, which saves operating procedures. In addition, the midsole ETPU and the outsole TPU are made of the same material, which makes it easier to melt and bond, thus forming a sole with strong interface adhesion. In addition, the sole materials of the same material are easier to recycle.
[0009] Optionally, the preparation method of the TPU bottom film is as follows: Pressing TPU pellets into TPU film at 200-210°C; Dispersing carbon nanotubes into polyvinyl alcohol solution, ultrasonically dispersing for 20-30 minutes, adding ultra-high molecular weight polyethylene fibers, ultrasonically dispersing for 20-30 minutes, filtering, and drying to obtain a fiber mesh layer, wherein the mass ratio of ultra-high molecular weight polyethylene fibers to carbon nanotubes is 1:0.1-0.3; At least one fiber mesh layer is placed on the upper and lower sides of the TPU film, respectively, and the number of fiber mesh layers is the same on both sides of the TPU film, and then hot-pressed at 130-140° C. and 0.034-0.04 MPa for 6-7 minutes to obtain a TPU bottom sheet.
[0010] By adopting the above technical scheme, the ultra-high molecular weight polyethylene fiber has high modulus and high strength, low density and high strength, good energy absorption, extremely low friction coefficient and excellent self-lubricating performance, so it has excellent wear resistance. The ultra-high molecular weight polyethylene fiber is ultrasonically dispersed in a polyvinyl alcohol solution containing carbon nanotubes, the ultra-high molecular weight polyethylene fibers are overlapped with each other, and the carbon nanotubes are attached to the surface of the ultra-high molecular weight polyethylene fiber. The carbon nanotubes themselves have excellent mechanical properties and can enhance the mechanical strength and wear resistance of the fiber. Moreover, when the carbon nanotubes are attached to the fiber surface, the contact area between the ultra-high molecular weight polyethylene fiber and the TPU film is increased. The stress can be effectively transferred from the carbon nanotubes and ultra-high molecular weight polyethylene fibers to the TPU film, ultimately improving the mechanical properties of the TPU film, such as tensile strength and elongation at break. In addition, the attachment of carbon nanotubes increases the roughness of the fibers, which can improve the friction between the fiber mesh layer and the ground, thereby improving its anti-slip performance. During hot pressing, polyvinyl alcohol can penetrate between the ultra-high molecular weight polyethylene fibers and carbon nanotubes and fully fit them, thereby increasing the bonding properties between the ultra-high molecular weight polyethylene fibers, carbon nanotubes and TPU film, and increasing the density of the fiber mesh layer, improving the overall mechanical strength of the TPU film, and thereby enhancing the tensile and tear resistance of the sole.
[0011] With TPU film as the central layer, the TPU film itself has excellent elasticity and tensile resistance. At least one fiber mesh layer is arranged on both sides thereof. After hot pressing, the TPU film and the fiber mesh layer can be bonded to each other. The fiber mesh layer formed by ultra-high molecular weight polyethylene fibers, carbon nanotubes and polyvinyl alcohol can further improve its tensile strength and tear resistance, and can also improve its wear resistance. With the increase of the number of fiber mesh layers, the mechanical strength can gradually increase, because when stretched by external force, the interface between the fiber mesh layer and the TPU film will debond, and holes will be formed between the TPU films. The pulling force gradually increases, and the TPU chain segments will fiberize. A large amount of energy is absorbed in the process of TPU fiberization and fiber mesh layer debonding, so that the TPU backsheet has higher tensile properties. Moreover, the attachment of carbon nanotubes can also increase the interfacial interaction between ultra-high molecular weight polyethylene fibers and TPU film, and improve the mechanical strength of the TPU backsheet. When the TPU backsheet is in contact with the ETPU particles for integral molding, the fiber mesh layer can be melt-bonded with the ETPU. One side of the fiber mesh layer is the TPU film, and the other side is the ETPU particles, which are fused through steam heating to obtain a tightly bonded outsole and midsole.
[0012] Optionally, the carbon nanotubes are pretreated as follows: The carbon nanotubes are dispersed in deionized water, cellulose nanofibers are added, and ultrasonic dispersion is performed for 20-30 minutes, followed by filtering and drying to obtain a carbon nanotube dispersion; The carbon nanotube dispersion is added to a mixed solution of isopropanol and deionized water, and ammonia water is added. After ultrasonication for 10-20 minutes, tetraethyl orthosilicate is added, and the mixture is reacted at 60-70° C. for 10-12 hours, washed, dried, and ground to obtain silica-coated particles. The mass ratio of the carbon nanotube dispersion to tetraethyl orthosilicate is 0.1:0.8-1. The silica-coated particles are dispersed in anhydrous ethanol, and ultrapure water, acetic acid and perfluorooctyltriethoxysilane are added after ultrasonic dispersion for 20-30 minutes, and the mixture is reacted at 70-80° C. for 4-5 hours, filtered and dried. The mass ratio of the silica-coated particles to perfluorooctyltriethoxysilane is 1:2-3.
[0013] By adopting the above technical scheme, cellulose nanofibers can act as dispersants due to their unique physical and chemical properties. When cellulose nanofibers are mixed with carbon nanotubes, they can interact with the surface of carbon nanotubes by physical adsorption and chemical bonding, thereby reducing the van der Waals interaction between carbon nanotubes, reducing agglomeration, and improving dispersibility. In addition, the carboxyl groups on the surface of nanocellulose can interact with the functional groups on the surface of carbon nanotubes to further enhance the dispersion effect. The cellulose nanofibers uniformly dispersed on the carbon nanotubes can also improve the overall strength of the material due to their high strength and high modulus, which helps to resist the external force during wear, thereby extending the service life of the carbon nanotubes. In addition, the cellulose nanofibers also have a certain lubricity, which helps to reduce the friction coefficient and wear during friction. The addition of cellulose nanofibers can increase the roughness of the carbon nanotube surface, thereby increasing the friction between the carbon nanotubes and ultra-high molecular weight polyethylene and enhancing the load fastness between the two. Then, ethyl orthosilicate is used to in-situ grow silicon dioxide with hydroxyl groups on the surface of the carbon nanotube dispersion, which can be composited with the cellulose nanofibers on the surface of the carbon nanotubes, and then through perfluorooctane The perfluorooctyltriethoxysilane is hydrolyzed to generate a hydroxyl structure at one section of the silane molecular chain. The generated hydroxyl group and the hydroxyl group on the surface of the silica undergo a dehydration condensation reaction, and the perfluorooctyltriethoxysilane is grafted onto the surface of the silica-coated particles in the form of a chemical covalent bond. Since the R group in the perfluorooctyltriethoxysilane molecular chain is a perfluorinated alkyl group, the pretreated carbon nanotubes have good hydrophobicity. Silica is coated on the carbon nanotubes containing nanocellulose. Since silica has high hardness, high wear resistance and thermal stability, it can increase the anti-skid and anti-wear effect of the carbon nanotubes. The grafting of perfluorooctyltriethoxysilane makes the silica coated on the surface of the carbon nanotubes hydrophobic, thereby reducing the adsorption performance of water molecules on the friction surface, weakening the lubricating effect of water, and further improving the anti-slip performance in wet and slippery environments; and the hydrophobic silica is coated on the carbon nanotubes, and the carbon nanotubes are loaded on ultra-high molecular weight polyethylene fibers. When the TPU film is hot-pressed and fused, the interface bonding force between the TPU hot-melt component and the carbon nanotubes can be increased, the bonding force between the fiber mesh layer and the TPU film can be improved, and the bonding strength between the TPU outsole and the ETPU midsole can also be improved.
[0014] Optionally, the ultra-high molecular weight polyethylene fiber is pretreated as follows: The plasma-treated ultra-high molecular weight polyethylene fiber is added to anhydrous ethanol, and nano-alumina and boron nitride are added, and ultrasonicated for 2-3 hours to form a dispersion; Add KH550 silane coupling agent solution to the dispersion, stir at 80-90°C for 4-5h, filter, wash and dry.
[0015] By adopting the above technical solution, nano-alumina has a large specific surface area and surface energy, and has high chemical activity and adsorption capacity. Boron nitride has excellent stability, friction resistance, and lubricity, and can play a good role in reducing friction during friction, and can also play a filling, strengthening and friction reducing effect. Because the molecular chain of ultra-high molecular weight polyethylene is a linear structure, there are only two elements of hydrogen and carbon on the main chain, the surface lacks polar groups, and the molecular structure with high crystallinity is very dense, resulting in low surface energy and high chemical inertness. It is difficult to form a TPU outsole with good bonding ability with the TPU film after hot pressing, so it is easy to cause the fiber mesh layer to be worn and separated from the sole. On the premise that the hot melt bonding force between the ultra-high molecular weight polyethylene fiber and the TPU film is improved by using polyvinyl alcohol to load carbon nanotubes on the surface of the ultra-high molecular weight polyethylene fiber, plasma treatment and other processes are still used to pre-modify the surface. Plasma treatment can significantly reduce its surface contact angle, increase surface energy, and introduce a large number of active functional groups such as -C=O, -OC=O, and -OH on its surface, thereby effectively improving the chemical properties of the fiber surface, improving its chemical reaction activity, and enhancing its surface wettability. Then, the KH550 molecular chain is used to load carbon nanotubes. The siloxane contained in the shoe can be hydrolyzed into silanol in water, which can form hydrogen bonds with the hydroxyl groups on the fiber after plasma treatment, and dehydrate and condense to form covalent bonds after heating, so that KH550 is grafted onto the surface of the ultra-high molecular weight polyethylene fiber. Nano-alumina and boron nitride also have hydroxyl groups, which can react with the other two hydroxyl groups on the silanol. Therefore, with KH550 as a bridge, the nano-alumina and boron nitride are chemically bonded to the ultra-high molecular weight polyethylene fiber, thereby achieving stable coating. In addition, the silanols between KH550 will also react, so that the molecular chains are interconnected to form a network structure, which covers the surface of the ultra-high molecular weight polyethylene fiber, enhances the interfacial force between the fiber and the TPU film, and enhances the bonding stability between the fiber mesh layer and the TPU film during wear, thereby improving the wear resistance of the sole and enhancing the bonding strength between the TPU outsole and the ETPU midsole.
[0016] Optionally, the mass ratio of the ultra-high molecular weight polyethylene fiber to nano-alumina and boron nitride is 1:0.1:0.01-0.05.
[0017] By adopting the above technical scheme, an appropriate amount of nano-aluminum oxide and boron nitride can be coated on the surface of ultra-high molecular weight polyethylene fibers, so that when in contact with the TPU film and the ETPU midsole, they can play a pinning role on the contact surface. When impacted, the rigid nano-aluminum oxide and boron nitride transfer stress between molecular chains, thereby dispersing the stress. At the same time, since the nano-aluminum oxide and boron nitride are relatively evenly coated on the surface of the ultra-high molecular weight polyethylene fibers, when external loads act on the TPU outsole, the high-strength nanoparticles can effectively improve the compressive strength of the ultra-high molecular weight polyethylene, thereby improving the wear resistance of the material.
[0018] Optionally, the amount of the KH550 silane coupling agent used is 10-20wt% of the total weight of the nano-alumina and boron nitride.
[0019] By adopting the above technical solution, KH550 silane coupling agent can be hydrolyzed to connect nano-alumina and boron nitride with ultra-high molecular weight polyethylene fibers, thereby improving the surface roughness of the ultra-high molecular weight polyethylene fibers, improving the interfacial adhesion between the fibers and the TPU film, and also improving the wear resistance of the fibers.
[0020] Optionally, the thickness of the TPU film is 0.1-0.2 mm.
[0021] By adopting the above technical scheme, a TPU film of appropriate thickness is used as the bonding center of the TPU backsheet, and the fiber mesh layers are hot-pressed on both sides to prepare the TPU backsheet. Since the TPU film has high strength and durability, it can withstand stronger impacts and extend the service life of the shoes. In addition, its thickness affects the flexibility of the sole. A thinner TPU film is more flexible, which can make the sole sufficiently flexible while maintaining sufficient stability.
[0022] Optionally, the thickness of the TPU bottom film is 0.3-0.8 mm.
[0023] By adopting the above technical solution, a TPU bottom sheet of appropriate thickness is used as the outsole. In a textured midsole molding mold, an outsole with certain patterns can be formed. There is no need to texture the TPU bottom sheet in advance, which saves production steps. In addition, a TPU bottom sheet of appropriate thickness can provide better wear resistance and anti-slip properties, thereby extending the service life of the shoes.
[0024] Optionally, the fiber mesh layer on one side of the TPU film is provided with three layers.
[0025] By adopting the above technical solution, the fiber mesh layer has the same thickness on both sides of the TPU film, and both are set to 3 layers, which can optimize the mechanical properties of the TPU bottom film.
[0026] Optionally, the water cooling time is 80-100s, and the water cooling pressure is 40-50N / m 2 .
[0027] By adopting the above technical solution, the foamed sole material is cooled with appropriate water cooling time and water cooling pressure, which can prevent the sole from being too hard, improve wearing comfort, improve the uniformity and density of the sole material, and improve wear resistance and resilience.
[0028] In summary, this application has the following beneficial effects: 1. Since the method of the present application adopts TPU film as the outsole, which is integrally molded with ETPU particles through steam, and uses a molding cavity containing a texture, the texture of the outsole can be produced while steam molding, which can save the process of pre-texturing the outsole and improve work efficiency. Moreover, the material of the TPU film is the same as that of the ETPU particles, so that the bonding strength between the outsole and the midsole is high, and it is conducive to the recycling of the sole material.
[0029] 2. In the present application, it is preferred to use carbon nanotubes loaded on the surface of ultra-high molecular weight polyethylene fibers as the fiber mesh layer, and hot-press TPU particles as the TPU film. The composite fiber mesh layer is hot-pressed on both sides of the TPU film to form a TPU backsheet. The fiber mesh layer can be firmly bonded to the TPU film, and during steam molding, the fiber mesh layer on one side of the TPU backsheet is firmly fused with the ETPU particles, thereby improving the peeling strength between the outsole and the midsole, while also enhancing the wear resistance and anti-slip properties of the sole, and improving the tensile and tear resistance of the sole.
[0030] 3. In the present application, cellulose nanofibers are preferably used to disperse carbon nanotubes, and then silicon dioxide is in situ coated on the carbon nanotube dispersion, and finally perfluorooctyltriethoxysilane is used for hydrophobic modification, which can increase the roughness of the surface of the carbon nanotubes, improve the interface between the ultra-high molecular weight polyethylene fibers and the TPU film and ETPU foamed particles, improve the bonding effect, and enhance the wear resistance and anti-slip effects.
[0031] 4. In the present application, nano-alumina, boron nitride and KH550 are preferably used to treat the ultra-high molecular weight polyethylene fiber after plasma treatment, and nano-alumina and boron nitride are coated on the surface to increase the contact area between the ultra-high molecular weight polyethylene fiber and the TPU film and ETPU foamed particles, thereby improving the anti-slip effect and wear resistance of the sole. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a cross-sectional view of the ETPU sole in Example 1 of the present application.
[0033] Figure 2 This is a cross-sectional view of the ETPU sole in the midsole molding mold.
[0034] Figure numerals: 1, TPU outsole; 2, ETPU midsole; 3, midsole molding mold; 31, upper mold cavity; 32, texture mold cavity; 33, air inlet channel; 34, exhaust channel; 35, positioning protrusion; 36, positioning hole; 37, exhaust hole; 38, vacuum exhaust channel. DETAILED DESCRIPTION
[0035] The following examples further illustrate the present application in detail.
[0036] Preparation Example 1-16 of TPU Backsheet In the preparation example, the TPU particles are selected from BASF of Germany, model 1185A, the ultra-high molecular weight polyethylene fibers are selected from Guangzhou Zhangdao Chemical, with a length of 12 mm and an equivalent diameter of 15-20 μm, the carbon nanotubes are selected from Sichuan Kenye, model KY-CNTs, the polyvinyl alcohol is PVA-1788, selected from Wuhan Runxingyuan Technology, the boron nitride is selected from Henan Yashun Chemical, product number 11-6, and the nano-alumina is selected from Jiangsu Tianxing New Materials, model TAP-A21, with a particle size of 40 nm.
[0037] Preparation Example 1: TPU particles were hot-pressed at 200° C. and 0.1 MPa to form a TPU film with a thickness of 200 μm as a TPU bottom sheet.
[0038] Preparation Example 2: (1) TPU particles were hot-pressed at 200°C and 0.1 MPa to form a TPU film with a thickness of 200 μm; (2) 3 g of carbon nanotubes were dispersed in a 3 wt% polyvinyl alcohol solution made from 3 g of polyvinyl alcohol, and 10 g of ultra-high molecular weight polyethylene fibers were added after ultrasonic dispersion for 30 min. After ultrasonic dispersion for 30 min, the mixture was filtered and dried at 80°C to obtain a fiber mesh layer; (3) Three layers of fiber mesh were placed on the upper and lower sides of the TPU film, respectively, and then pressed at 140°C and 0.04 MPa for 6 min to produce a TPU bottom sheet with a thickness of 0.8 mm.
[0039] Preparation Example 3: (1) TPU particles were hot-pressed at 210° C. and 0.06 MPa to form a TPU film with a thickness of 200 μm; (2) 1 g of carbon nanotubes was dispersed in a 3 wt% polyvinyl alcohol solution made from 3 g of polyvinyl alcohol, and after ultrasonic dispersion for 20 min, 10 g of ultra-high molecular weight polyethylene fibers were added, and after ultrasonic dispersion for 20 min, the mixture was filtered and dried at 80° C. to obtain a fiber mesh layer; (3) A layer of fiber mesh is placed on the upper and lower sides of the TPU film respectively, and then pressed at 130°C and 0.04 MPa for 7 minutes to produce a TPU bottom sheet with a thickness of 0.4 mm.
[0040] Preparation Example 4: The difference from Preparation Example 2 is that two fiber mesh layers are placed on the upper and lower sides of a 200 μm thick TPU film, respectively, and pressed at 140°C and 0.04 MPa for 6 minutes to form a 0.6 mm thick TPU film.
[0041] Preparation Example 5: The difference from Preparation Example 2 is that the TPU particles are hot pressed at 200°C and 0.06 MPa to form a 100μm TPU film, a fiber mesh layer is placed on the upper and lower sides of the TPU film respectively, and pressed at 130°C and 0.034 MPa for 6 minutes to form a TPU film with a thickness of 0.3mm.
[0042] Preparation Example 6: The difference from Preparation Example 2 is that only one fiber mesh layer is placed on one side of the TPU film with a thickness of 200 μm, and it is pressed at 130°C and 0.034 MPa for 6 minutes to make a TPU backsheet with a thickness of 0.3 mm.
[0043] Preparation Example 7: The difference from Preparation Example 2 is that the carbon nanotubes are pretreated as follows: (1) Dispersing 10 g of carbon nanotubes into 90 g of deionized water, adding 5 g of cellulose nanofibers, and ultrasonically dispersing for 20 min, filtering, and drying to obtain a carbon nanotube dispersion; (2) adding 0.5 g of the carbon nanotube dispersion to a mixed solution of 6 g of isopropanol and 4 g of deionized water, adding 2 g of ammonia water and then ultrasonically dispersing for 20 min, adding 5 g of ethyl orthosilicate, reacting at 60° C. for 12 h, washing with deionized water and ethanol, drying at 70° C., and grinding to obtain silica-coated particles; (3) 0.5 g of silica-coated particles were dispersed in 100 ml of anhydrous ethanol, and then ultrasonically dispersed for 20 min, 2 ml of ultrapure water, 2 ml of acetic acid and 1 g of perfluorooctyltriethoxysilane were added, and the mixture was reacted at 70° C. for 5 h, filtered and dried.
[0044] Preparation Example 8: The difference from Preparation Example 2 is that the carbon nanotubes are pretreated as follows: (1) Dispersing 10 g of carbon nanotubes into 90 g of deionized water, adding 10 g of cellulose nanofibers, and ultrasonically dispersing for 30 min, filtering, and drying to obtain a carbon nanotube dispersion; (2) adding 0.5 g of the carbon nanotube dispersion to a mixed solution of 6 g of isopropanol and 4 g of deionized water, adding 2 g of ammonia water and then ultrasonically dispersing for 20 min, adding 4 g of ethyl orthosilicate, reacting at 70° C. for 10 h, washing with deionized water and ethanol, drying at 70° C., and grinding to obtain silica-coated particles; (3) 0.5 g of silica-coated particles were dispersed in 100 ml of anhydrous ethanol, and then ultrasonically dispersed for 30 min, 2 ml of ultrapure water, 2 ml of acetic acid and 1.5 g of perfluorooctyltriethoxysilane were added, and the mixture was reacted at 80° C. for 4 h, filtered and dried.
[0045] Preparation Example 9: The difference from Preparation Example 7 is that silica coating was not used. 0.5 g of carbon nanotube dispersion was added to 100 ml of anhydrous ethanol. After ultrasonic dispersion for 30 min, 2 ml of ultrapure water, 2 ml of acetic acid and 1.5 g of perfluorooctyltriethoxysilane were added. The mixture was reacted at 80°C for 4 h, filtered and dried.
[0046] Preparation Example 10: The difference from Preparation Example 7 is that 0.5 g of carbon nanotubes is dispersed in 100 ml of anhydrous ethanol, and after ultrasonic dispersion for 30 min, 2 ml of ultrapure water, 2 ml of acetic acid and 1.5 g of perfluorooctyltriethoxysilane are added, reacted at 80° C. for 4 h, filtered and dried.
[0047] Preparation Example 11: The difference from Preparation Example 7 is that the silica-coated particles are not treated with perfluorooctyltriethoxysilane, pure water and acetic acid.
[0048] Preparation Example 12: The difference from Preparation Example 7 is that the ultra-high molecular weight polyethylene fiber is pretreated by the following method: 10 g of ultra-high molecular weight polyethylene fiber is added to 50 g of anhydrous ethanol after being treated with plasma, 1 g of nano-alumina and 0.5 g of boron nitride are added, and ultrasonic treatment is performed for 3 h to form a dispersion liquid. The plasma treatment power is 30 W and the treatment time is 3 min. KH550 silane coupling agent solution was added to the dispersion, stirred at 80°C for 5h, filtered, washed three times with anhydrous ethanol, and dried at 110°C for 8h. The KH550 silane coupling agent solution was prepared by mixing 0.3g KH550 and 12g deionized water, adjusting the solution to acidity with glacial acetic acid, and stirring for 10min.
[0049] Preparation Example 13: Ultra-high molecular weight polyethylene fiber was pretreated by the following method: 10 g of ultra-high molecular weight polyethylene fiber was added to 50 g of anhydrous ethanol after being treated with plasma, and 1 g of nano-alumina and 0.1 g of boron nitride were added, and ultrasonicated for 2 h. To form a dispersion, the plasma treatment power is 30 W and the treatment time is 3 min; KH550 silane coupling agent solution was added to the dispersion, stirred at 90°C for 4h, filtered, washed three times with anhydrous ethanol, and dried at 110°C for 8h. The KH550 silane coupling agent solution was prepared by mixing 0.11g KH550 and 6g deionized water, adjusting the solution to acidity with glacial acetic acid, and stirring for 10min.
[0050] Preparation Example 14: The difference from Preparation Example 12 is that no nano-alumina and boron nitride are added.
[0051] Preparation Example 15: The difference from Preparation Example 12 is that an equal amount of nano-alumina is used instead of boron nitride.
[0052] Preparation Example 16: The difference from Preparation Example 12 is that no KH550 silane coupling agent solution is added, and the dispersion is dried at 110° C. for 8 h. Example
[0053] Embodiment 1: A process for making an ETPU sole, comprising the following steps: S1. Making TPU outsole 1: Cutting the TPU bottom sheet into a desired shape to obtain TPU outsole 1, wherein the TPU bottom sheet is made according to Preparation Example 1.
[0054] S2, main material: lay the TPU outsole 1 on the bottom of the midsole molding mold 3 containing the textured mold cavity 32, and then fill the midsole molding mold 3 with ETPU foaming particles, so that the ETPU foaming particles are laid on the TPU outsole 1, and the ETPU particles are selected from Fujian Read Chemical Technology, and the brand is READCHEM.
[0055] S3, steam molding: steam is introduced into the midsole molding mold 3 to mold the ETPU particles into the ETPU midsole 2, the molding pressure is 0.3MPa, the molding temperature is 160°C, the molding time is 150s, and then the venting, water cooling, and demolding are performed to obtain the ETPU sole in which the TPU outsole 1 and the ETPU midsole 2 are bonded to each other. The specific structure is as follows Figure 1 As shown, the water cooling time is 80s and the water cooling pressure is 40N / m 2 .
[0056] See also Figure 2 The midsole molding mold 3 includes an upper mold cavity 31 and a texture mold cavity 32 that cooperate with each other. The bottom surface of the texture mold cavity 32 is provided with a pattern for forming a texture on the lower surface of the TPU outsole 1. The upper mold cavity 31 is provided with an air inlet channel 33 for introducing steam into the texture mold cavity 32, and an exhaust channel 34 for discharging steam from the texture mold cavity 32; a plurality of positioning protrusions 35 for positioning the TPU outsole are provided on the bottom surface of the texture mold cavity 32. In this embodiment, three positioning protrusions are taken as an example. After steam molding, under the action of pressure, the TPU The outsole 1 is in close contact with the bottom surface of the texture mold cavity 32, the positioning protrusion 35 squeezes the TPU outsole 1, and forms a positioning hole 36 on the TPU outsole; the positioning protrusion 35 is provided with an exhaust hole 37 connected to the inside of the texture mold cavity 32, which is used to remove the steam between the TPU outsole 1 and the positioning protrusion 35; and the bottom surface of the texture mold cavity 32 is provided with a vacuum exhaust channel 38 for removing the air between the TPU outsole 1 and the texture mold cavity 32, which is beneficial to the clear forming of the texture on the TPU outsole 1, and is also beneficial to the limited fitting of the TPU outsole 1 in the texture mold cavity 32.
[0057] Embodiment 2: A manufacturing process of ETPU sole, which differs from Embodiment 1 in that it comprises the following steps: S1. Making TPU outsole 1: Cutting the TPU bottom sheet into a desired shape to obtain TPU outsole 1, wherein the TPU bottom sheet is made according to Preparation Example 1.
[0058] S2, main material: laying the TPU outsole 1 on the bottom of the midsole forming mold 3 containing the textured mold cavity 32, and then filling the midsole forming mold 3 with ETPU foaming particles so that the ETPU foaming particles are laid on the TPU outsole 1.
[0059] S3, steam molding: steam is introduced into the midsole molding mold 3 to mold the ETPU particles into the ETPU midsole 2, the molding pressure is 0.1MPa, the molding temperature is 120℃, the molding time is 190s, and then exhaust, water-cooled, and demolded to obtain the ETPU sole, the water-cooling time is 100s, and the water-cooling pressure is 50N / m 2 .
[0060] Example 3: A process for producing an ETPU sole, which differs from Example 1 in that the TPU bottom sheet is produced by Preparation Example 2.
[0061] Example 4: A process for manufacturing an ETPU sole, which differs from Example 1 in that the TPU bottom sheet is made from Preparation Example 3.
[0062] Example 5: A process for manufacturing an ETPU sole, which differs from Example 3 in that the TPU bottom film is made from Preparation Example 4.
[0063] Example 6: A process for producing an ETPU sole, which differs from Example 3 in that the TPU bottom sheet is produced by Preparation Example 5.
[0064] Example 7: A process for manufacturing an ETPU sole, which differs from Example 3 in that the TPU bottom sheet is made from Preparation Example 6.
[0065] Example 8: A process for producing an ETPU sole, which differs from Example 3 in that the TPU bottom sheet is produced by Preparation Example 7.
[0066] Example 9: A process for producing an ETPU sole. The difference from Example 3 is that the TPU bottom sheet is produced by Preparation Example 8.
[0067] Example 10: A process for producing an ETPU sole, which differs from Example 8 in that the TPU bottom sheet is produced by Preparation Example 9.
[0068] Example 11: A process for manufacturing an ETPU sole, which differs from Example 8 in that the TPU bottom sheet is made from Preparation Example 10.
[0069] Example 12: A process for producing an ETPU sole, which differs from Example 8 in that the TPU bottom sheet is produced by Preparation Example 11.
[0070] Example 13: A process for producing an ETPU sole, which differs from Example 8 in that the TPU bottom sheet is produced by Preparation Example 12.
[0071] Example 14: A process for manufacturing an ETPU sole, which differs from Example 8 in that the TPU bottom film is made from Preparation Example 13.
[0072] Example 15: A process for producing an ETPU sole, which differs from Example 13 in that the TPU bottom sheet is produced by Preparation Example 14.
[0073] Example 16: A process for producing an ETPU sole, which differs from Example 13 in that the TPU bottom sheet is produced by Preparation Example 15.
[0074] Example 17: A process for manufacturing an ETPU sole, which differs from Example 13 in that the TPU bottom sheet is made from Preparation Example 16.
[0075] Comparative Example Comparative Example 1: A manufacturing process of an ETPU sole, which differs from Example 1 in that a nitrile rubber outsole is used instead of the TPU outsole 1, the thickness of the nitrile rubber outsole is 0.2 mm, and it is made by hot pressing nitrile rubber powder at 160°C and 2 MPa. The nitrile rubber powder is selected from Shenzhen Wansuyuan Rubber and Plastic, model MY60M, item number 002, and particle size 120 mesh.
[0076] Performance testing The ETPU sole was prepared according to the method of the embodiment and the comparative example, and the various properties of the sole were tested according to the following method, and the test results were recorded in Table 1.
[0077] 1. Peel strength: Use a tensile testing machine to test the interfacial adhesion between the TPU outsole and the ETPU midsole through a peel test. The tensile speed is 100 mm / min and the test time is 150 s. Under the same conditions, record at least 5 samples and take the average value.
[0078] 2. Anti-slip coefficient: Tested in accordance with HG / T3780-2005 "Test method for static anti-slip performance of footwear".
[0079] 3. DIN wear: Tested in accordance with GB / T9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method)", the test force is (10±0.2)N, the rotation speed is (40±1)r / min.
[0080] 4. Tear strength: Tested in accordance with GB / T3903.12-2005 "Test method for tear strength of footwear outsoles" at a test speed of 500m / min.
[0081] 5. Tensile strength: Tested in accordance with GB / T6344-1996 "Determination of tensile strength and elongation at break of soft foam polymer materials".
[0082] Table 1 Performance test results of ETPU sole Combining the data in Table 1 and Examples 1-2, it can be seen that when only TPU film is used as the outsole and the sole is prepared by integrally molding and foaming with ETPU particles, the peeling strength of the TPU outsole and the ETPU midsole in the sole is large, which is higher than that in Comparative Example 1 where rubber is used as the outsole and ETPU particles are used as the midsole. This shows that the TPU outsole and the ETPU particles have good compatibility when integrally molded, can be tightly bonded, and the two materials are the same, which can be easily recycled. In addition, a mold cavity containing a pattern is provided in the molding mold, and there is no need to prepare the pattern on the outsole first, and the operation is simpler, but the wear resistance and slip resistance of the prepared sole are not as good as those of the sole made of the rubber outsole.
[0083] In Example 3 and Example 4, the TPU bottom sheets prepared in Preparation Example 2 and Preparation Example 3 are respectively used as TPU outsoles after cutting, and the TPU film formed by hot pressing with ultra-high molecular weight polyethylene fibers and carbon nanotubes is composited and hot-pressed with TPU particles to form the TPU bottom sheet. Three fiber mesh layers are provided on both sides of the TPU film. Table 1 shows that in the soles prepared in Example 3 and Example 4, the peel strength of the TPU outsole and the ETPU midsole is further improved, and the anti-slip coefficient is increased, the anti-slip performance is improved, the DIN wear is reduced, the wear resistance is improved, and the overall tear resistance and tensile resistance of the sole are stronger.
[0084] In Example 5, the TPU outsole prepared in Preparation Example 4 is used. Compared with Preparation Example 2 in Example 3, only two fiber mesh layers are set on the upper and lower sides of the TPU film, and the thickness of the overall TPU bottom film is reduced. It can be seen that the peeling strength of the prepared sole material is slightly reduced, the anti-slip coefficient does not change much, but the wear resistance, tear resistance and tensile resistance are slightly weakened.
[0085] Compared with Example 3, Example 6 adopts the TPU backsheet made in Preparation Example 5. Compared with Preparation Example 2, in Preparation Example 5, only one fiber mesh layer is placed on both sides of the TPU film. Table 1 shows that the peeling strength, anti-slip and wear resistance of the sole prepared in Example 6 are reduced, and the tensile and tear resistance are worse.
[0086] In Example 7, the TPU backsheet prepared in Preparation Example 6 is used. In Preparation Example 6, only one fiber mesh layer is set on one side of the TPU film. Compared with Example 3 and Examples 5-6, the anti-slip and wear resistance of the sole prepared in Example 7 decreases, and the tensile and tear resistance decreases.
[0087] In Example 8 and Example 9, the TPU backsheets prepared in Preparation Example 7 and Preparation Example 8 are used respectively. Compared with Preparation Example 2 in Example 3, the carbon nanotubes are pretreated with cellulose nanofibers, etc. It can be seen that in the soles prepared in Example 8 and Example 9, the peel strength of the TPU outsole and the ETPU midsole is slightly increased, the anti-slip effect is enhanced, and the DIN wear is reduced, the wear resistance is improved, and the tensile and tear resistance effects are further improved.
[0088] In Example 10, the TPU backsheet prepared in Preparation Example 9 is used. Compared with Preparation Example 7 in Example 8, tetraethyl orthosilicate is not used to in-situ synthesize silica on the carbon nanotube dispersion, and perfluorooctyltriethoxysilane is used to perform hydrophobic treatment on the carbon nanotube dispersion. It can be seen that the wet anti-slip coefficient of the sole is not much different from that in Example 8, but the dry anti-slip coefficient and wear resistance are reduced. This shows that coating silica particles on the carbon nanotube dispersion can increase the wear resistance, anti-slip effect and tensile strength of the fiber mesh layer.
[0089] Compared with Example 8, Example 11 uses the TPU backsheet made in Preparation Example 10. Compared with Preparation Example 7, cellulose nanofibers are not used to disperse the carbon nanotubes, and the silica particles are not coated. The carbon nanotubes are only hydrophobically modified. The data in Table 1 show that various properties of the sole prepared in Example 11 are affected, and the wear resistance and anti-slip properties are reduced.
[0090] In Example 12, the TPU film prepared in Preparation Example 11 was used. Compared with Preparation Example 7 in Example 8, perfluorooctyltriethoxysilane was not used for hydrophobic treatment during the pretreatment of carbon nanotubes. It can be seen that its wet anti-slip coefficient decreased, the peel strength weakened, and the tensile and tear resistance properties decreased.
[0091] Compared with Example 8, Examples 13 and 14 use the TPU backsheets prepared in Preparation Examples 12 and 13, respectively. Compared with Preparation Example 7, the ultra-high molecular weight polyethylene fibers are further pretreated with nano-alumina, boron nitride, etc. The data in Table 1 show that in the soles prepared in Examples 13 and 14, the peel strength of the TPU outsole and the ETPU midsole is increased, and the anti-slip and wear resistance are improved, and the tensile and tear resistance effects are enhanced.
[0092] In Example 15, the TPU backsheet prepared in Preparation Example 14 is used. Compared with Preparation Example 12 in Example 13, nano-aluminum oxide and boron nitride are not added. From the comparison of data in Table 1, it can be seen that the peel strength of the sole, TPU outsole and ETPU midsole prepared in Example 15 is reduced, and the wear resistance and anti-slip properties are reduced.
[0093] Compared with Example 13, Example 16 adopts the TPU backsheet made in Preparation Example 15. Compared with Preparation Example 12, nano-alumina is used instead of boron nitride. Although its anti-slip performance is improved, the wear amount is increased.
[0094] In Example 17, the TPU backsheet prepared in Preparation Example 16 was used. Compared with Preparation Example 12 in Example 13, no KH550 silane coupling agent solution was added. The data in Table 1 show that the anti-slip and wear resistance of the sole prepared in Example 17 are reduced.
[0095] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A process for making ETPU soles, characterized in that: The production steps include: Making a TPU outsole (1): cutting the TPU bottom sheet into a desired shape to obtain a TPU outsole (1); Injection: Laying the TPU outsole (1) in a midsole forming mold (3) containing a textured mold cavity (32), and then filling the midsole forming mold (3) with ETPU foaming particles so that the ETPU foaming particles are laid on the upper surface of the TPU outsole (1); Steam molding: Steam is introduced into the midsole molding mold (3) to mold the ETPU particles into the ETPU midsole (2). The molding pressure is 0.1-0.3MPa, the molding temperature is 120-160°C, and the molding time is 150-190s. Then, the mold is vented, water-cooled, and demolded to obtain the ETPU sole.
2. The manufacturing process of the ETPU sole according to claim 1, characterized in that: The preparation method of the TPU back sheet is as follows: Pressing TPU pellets into TPU film at 200-210°C; Dispersing carbon nanotubes into polyvinyl alcohol solution, ultrasonically dispersing for 20-30 minutes, adding ultra-high molecular weight polyethylene fibers, ultrasonically dispersing for 20-30 minutes, filtering, and drying to obtain a fiber mesh layer, wherein the mass ratio of ultra-high molecular weight polyethylene fibers to carbon nanotubes is 1:0.1-0.3; At least one fiber mesh layer is placed on the upper and lower sides of the TPU film, and the number of fiber mesh layers is the same on both sides of the TPU film. The film is then hot-pressed at 130-140° C. and 0.034-0.04 MPa for 6-7 minutes to obtain a TPU backing sheet.
3. The manufacturing process of the ETPU sole according to claim 2, characterized in that: The carbon nanotubes are pretreated as follows: The carbon nanotubes are dispersed in deionized water, cellulose nanofibers are added, and ultrasonic dispersion is performed for 20-30 minutes, followed by filtering and drying to obtain a carbon nanotube dispersion; The carbon nanotube dispersion is added to a mixed solution of isopropanol and deionized water, and ammonia water is added. After ultrasonication for 10-20 minutes, tetraethyl orthosilicate is added, and the mixture is reacted at 60-70° C. for 10-12 hours, washed, dried, and ground to obtain silica-coated particles. The mass ratio of the carbon nanotube dispersion to tetraethyl orthosilicate is 0.1:0.8-1. The silica-coated particles are dispersed in anhydrous ethanol, and ultrapure water, acetic acid and perfluorooctyltriethoxysilane are added after ultrasonic dispersion for 20-30 minutes, and the mixture is reacted at 70-80° C. for 4-5 hours, filtered and dried. The mass ratio of the silica-coated particles to perfluorooctyltriethoxysilane is 1:2-3.
4. The manufacturing process of the ETPU sole according to claim 2, characterized in that: The ultra-high molecular weight polyethylene fiber is pre-treated as follows: The plasma-treated ultra-high molecular weight polyethylene fiber is added to anhydrous ethanol, and nano-alumina and boron nitride are added, and ultrasonic treatment is performed for 2-3 hours to form a dispersion; Add KH550 silane coupling agent solution to the dispersion, stir at 80-90°C for 4-5h, filter, wash and dry.
5. The manufacturing process of the ETPU sole according to claim 4, characterized in that: The mass ratio of the ultra-high molecular weight polyethylene fiber to the nano-alumina and boron nitride is 1:0.1:0.01-0.
05.
6. The manufacturing process of the ETPU sole according to claim 4, characterized in that: The amount of the KH550 silane coupling agent used is 10-20wt% of the total weight of the nano-alumina and boron nitride.
7. The manufacturing process of the ETPU sole according to claim 2, characterized in that: The thickness of the TPU film is 0.1-0.2 mm.
8. The manufacturing process of the ETPU sole according to claim 7, characterized in that: The thickness of the TPU bottom film is 0.3-0.8 mm.
9. The manufacturing process of the ETPU sole according to claim 2, characterized in that: The fiber mesh layer on one side of the TPU film is provided with three layers.
10. The manufacturing process of the ETPU sole according to claim 1, characterized in that: The water cooling time is 80-100s, and the water cooling pressure is 40-50N / m 2 .
Citation Information
Cited By
Recyclable adhesive-free integrally formed sole and mold for manufacturing same
WO2026137661A1